Investigation Into Antioxidant and Antinuclear Effect and Mechanism of Sesamum Indicum Leaves in a Rodent Model - Maheen Faheem, Bilal Hassan, Sadaf Sajid, Nadeem Yaqoob, Rao Salman Aziz, Javeria Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: An ethanolic extract of Sesamum indicum Linn was used to test for phytochemicals, antioxidant activity, and gastroprotective effects. Study Design: Cross-Sectional Study Place of Study: Rashid Latif Medical College Lahore. Duration of Study: July 2021 to March 2022 Materials and methods: This study ulcerated Wister albino rats using pylorus ligation and indomethacin-induced ulcer screening. Ulceration required pylorus ligation. These ulcer screening models were used. An ethanolic S. indicum leaves (EESIL) at 100, 200, and 400 mg/kg (orally for 7 days) was compared against omeprazole, a common ulcer medication. The trial lasted seven days. Throughout the course of the experiment, readings were taken for the following variables: stomach content; pH; total acidity; pepsin activity ulcer score; free acidity; ulcer index (UI); percentage of inhibition of ulcers; mean mucin, pepsin, and total protein content; and ulcer index (UI). Results: In comparison to the control group, the pylorus ligation model resulted in a decrease in pepsin activity, free acidity, pepsin content, ulcer score, total protein content, and % ulcer inhibition. Moreover, the overall acidity level was lower (P< 0.05 and P< 0.01). EESIL-tested groups had higher mean mucin and stomach content pH (P 0.05 and P 0.01). Both findings are statistically significant. EESIL dosages (100, 200, and 400 mg/kg ) had dose-dependent gastroprotective effects. Compared to the control group, stomach metrics like UI and ulcer score dropped significantly (P< 0.05 and P<0.01), gastric pH increased, and ulcer percentage inhibition increased. Increased ulcer inhibition percentage. Moreover, stomach pH increased and ulcer percentage decreased. Conclusion: Antioxidant, anti-ulcer, EESIL, and EESIL compounds have antioxidant action depending on concentration. Antioxidant is connected. The study found that the EESIL's increased defensive and decreased offensive components increased its antiulcer potential. This was due to the study's revisions. The research's offensive and defensive design caused this. Keywords: Antioxidant, anti-ulcer, ethanolic extract of sesamum indicum leaves, indomethacin, pylorus ligation, ulcer index